Urolithiasis Develops Endothelial Dysfunction as a Clinical Feature - Javier Sáenz-Medina; María Martinez; Silvia Rosado; Manuel Durán; Dolores Prieto; Joaquín Carballido (MDPI AG, 2021)
An increased risk of cardiovascular morbidity has been reported in lithiasic patients. In this context, endothelial dysfunction (ED), an earlier status of atherogenesis, has been identified in hyperoxaluria rat models of urolithiasis. Objective: The purpose of this study was to determine the endothelial vascular function in patients with urolithiasis in relation to systemic inflammatory, oxidative stress, and vascular function serum markers. Methods: A cross-sectional study was performed between 27 urolithiasic patients, matched for age and sex, with 27 healthy patients. Endothelial function was assessed by measuring flow-mediated dilation (Celermajer method). Fasting blood was collected to determine metabolic parameters (glucose and lipid profile), along with serum CRP, IL-6, MDA, ADMA, and VCAM-1. Results: Both the control and urolithiasis groups were homogenous in anthropometric, exploration, and general laboratory measures. Flow-mediated dilation (%FMD) was 11.85% (SE: 2.78) lower in the lithiasis group (p < 0.001). No significant differences were achieved between groups when CRP, IL-6, MDA, ADMA, and VCAM-1 were compared, although slightly higher values of CRP, ADMA, and VCAM-1 were detected in the lithiasic group. A correlation was not reached in any of the serum markers when they were related to flow-mediated values, although a slight negative correlation trend was observed in MDA, VCAM-1, and IL-6 values. Conclusions: Endothelial dysfunction constitutes an important disorder related to urolithiasis patients. It must be considered as an early feature responsible for future cardiovascular events. Our study did not find a significant association between inflammatory, oxidative stress, endothelial serum markers, and flow-mediated dilation.